(untitled) (Fiep Bulletin - online, 2014)
The teaching of first aid is still little widespread, underscoring the importance of actions addressing this topic for the entire community. During this study were carried out educational practices in health addressing the topic with students and teachers of a public school in Western Paraná, with the goal of empowering them to act properly against the urgency and emergency situations. In this way, the work was conducted in two phases. First, at the request of the school, was held the educational practice with teachers, where academia spoke on the topic, emphasizing the main incidents that take place in the school environment. Several questions arose during exposure of the contents, demonstrating the unpreparedness of these professionals in attendance the victim of an accident. In a second moment, health education was geared to students, with an emphasis on cardiopulmonary arrest and actions against the problem. Several students performed chest compressions and ventilation during the demonstrative class. At the end of these practices we can conclude that students and teachers have weaknesses to act in emergency situations pointing out the need to address continually the topic in schools.